2017
DOI: 10.1007/978-3-319-49674-0_17
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials Made from Coiled-Coil Peptides

Abstract: The development of biomaterials designed for specific applications is an important objective in personalized medicine. While the breadth and prominence of biomaterials have increased exponentially over the past decades, critical challenges remain to be addressed, particularly in the development of biomaterials that exhibit highly specific functions. These functional properties are often encoded within the molecular structure of the component molecules. Proteins, as a consequence of their structural specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…In a pioneering work, Kim and co-workers established that a much shorter sequence derived from the transcriptional activator GCN4 leucine zipper, composed only of 32 amino acids, can form stable dimers in which the interface between adjacent helices is stabilized by KIH packing . The high-resolution X-ray crystal structure of this sequence afforded detailed insights on KIH packing and provided an excellent paradigm to study the peptide sequence to structure relationship and the design of nanomaterials. ,, Consequently, leucine zipper-based peptide modules allowed the successful design of diverse nanostructures, including nanofibers, , nanotubes, spheres, and sheetlike structures with a multitude of functionalities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a pioneering work, Kim and co-workers established that a much shorter sequence derived from the transcriptional activator GCN4 leucine zipper, composed only of 32 amino acids, can form stable dimers in which the interface between adjacent helices is stabilized by KIH packing . The high-resolution X-ray crystal structure of this sequence afforded detailed insights on KIH packing and provided an excellent paradigm to study the peptide sequence to structure relationship and the design of nanomaterials. ,, Consequently, leucine zipper-based peptide modules allowed the successful design of diverse nanostructures, including nanofibers, , nanotubes, spheres, and sheetlike structures with a multitude of functionalities.…”
mentioning
confidence: 99%
“…Coiled-coil proteins are composed of recurring sequences of seven amino acids, known as heptad repeats, and the majority these proteins require a minimum of three to four heptad repeats or 21–28 residue peptide chains to stabilize the dimeric helical interface. , Accordingly, until now, all of the coiled-coil peptide-based nanomaterials are composed of chain lengths having more than three heptad repeats. However, a close analysis revealed that a single repeat can accommodate more than one KIH packed side chains from adjacent helices. ,, These insights prompted us to investigate whether the highly stabilizing KIH packing has the potential to act as an oligomerization module for helical sequences consisting of only seven residues or a single heptad repeat (SHR).…”
mentioning
confidence: 99%
“…Coiled-coil peptides are structural sequences common in fibrous proteins, which consists of more than two α-helices [ 81 ]. Typically, the primary structure of the α-helices consists of (a-b- c -d-e-f-g) n , where “a” and “d” are usually occupied by hydrophobic amino acids, such as leucine and valine, “e” and “g” are occupied by charged residues [ 82 ]. Similar to functional groups, adaptable hydrogels could be formed by self-assembly of polymers grafted with coiled-coil peptides, or by crosslink of micelles that consist of peptide-grafted polymers with reactive groups [ 83 ].…”
Section: Reversible Linkages For Adaptable Hydrogelsmentioning
confidence: 99%
“…Over the last decades, due to the advancement of technology (artificial intelligence or robotics) [ 1 ], wide novel, multifunctional, and biomimetic biomaterials (natural, modified natural, or synthetic) have been developed [ 2 ] with enhanced properties and applications [ 3 ] suitable for use in areas from the food industry to regenerative medicine and bioprinting [ 4 ]. These biomaterials can be successfully substitute for the traditional materials [ 5 ].…”
Section: Introductionmentioning
confidence: 99%